Altered hierarchical organization between empathy and gambling networks in disordered gamblers - Zhou, Hui; He, Yuwen; Yuan, Zhen; Zhou, Yuan; Yin, Jingwen; Chark, Robin; Fong, Davis Ka Chio; Fong, Lawrence Hoc Nang; Wu, Anise M. S. (Frontiers in Psychiatry, 2023)
Background: Despite the demonstrated association between empathy and gambling at the behavioral level, limited neuroimaging research on empathy and gambling disorder has been conducted. Whether and how the brain network of empathy and that of gambling interact in disordered gamblers has not been investigated. This study aimed to address this research gap by examining the hierarchical organizational patterns, in which the differences of causal interactions of these networks between disordered gamblers and healthy controls were revealed. Methods: Resting-state fMRI data of 32 disordered gamblers and 56 healthy controls were included in the formal analysis. Dynamic causal modeling was used to examine the effective connectivity within and between empathy and gambling networks among all participants. Results: All participants showed significant effective connectivity within and between empathy and gambling networks. However, compared with healthy controls, disordered gamblers displayed more excitatory effective connectivity within the gambling network, the tendency to display more excitatory effective connectivity from the empathy network to the gambling network, and reduced inhibitory effective connectivity from the gambling network to the empathy network. Conclusions: The exploratory study was the first to examine the effective connectivity within and between empathy and gambling networks among disordered gamblers and healthy controls. These results provided insights into the causal relationship between empathy and gambling from the neuroscientific perspective and further confirmed that disordered gamblers show altered effective connectivity within and between these two brain networks, which may be considered to be a potential neural index for gambling disorder (GD) identification. In addition, the altered interactions between empathy and gambling networks may also indicate the potential targets for the neuro-stimulation intervention approach (e.g., transcranial magnetic stimulation).